The empty house - Doyle, Conan Arthur; Alex Woolf (London: Arcturus, 2022)
Join world-famous detective Sherlock Holmes and his ever-loyal sidekick Dr. Watson as they embark on a daring adventure. The whole of London is shocked and baffled by the murder of Ronald Adair. It seems like an impossible crime! Can our sensational sleuth solve the mystery of how Adair was killed before the murderer strikes again? This thrilling tale has been retold and adapted with new illustrations, making it perfect for younger readers.